RELASI MAJELIS ULAMA INDONESIA (MUI) DAN KEKUASAAN NEGARA PADA MASA ORDE BARU DALAM PANDANGAN LOUIS ALTHUSSER - Anugrah, Dendy Wahyu; Fadlullah, Muhammad Endy (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2024)
Since its establishment, the Indonesian Council of Ulama (MUI) has a very significant role in the life of Indonesian society, especially for Muslims. Through two media that are always presented, namely fatwa (legal result) and discourse, MUI's existence is authoritative in the spectrum of Islamic religion in Indonesia. Historically, MUI is faced with the political situation that occurred during the New Order era. The relationship between MUI and the New Order government needs to be traced and analysed further in order to provide a holistic understanding. To analyse and know how the relation between MUI and state power during the New Order, this research is based on the thought of a contemporary French philosopher, Louis Althusser with his concept of ideology. The method in this research uses library research related to the object of research. Finally, this research shows that the relationship between MUI and the state during the New Order era was political. As a religious (Islamic) institution, MUI was used as one of the ideological tools of the state to legitimise the political interests of power. As stated by Althusser, that religious institution is one of the ideological instruments of the state to control the society that is often not realised by the society itself.